Psychosocial factors as correlates of reading achievement of students with hearing impairment in Ibadan, Oyo State, Nigeria (2020)
This study examined the psychological and social factors as correlates of reading achievement of students with hearing impairment in secondary school in Ibadan, Oyo state, Nigeria. The descriptive survey research design of correlational type was adopted. A total of 62 students with hearing impairment from secondary schools in Ibadan, Oyo state were selected using purposive sampling technique. The instrument used for collection of data was a questionnaire tagged Students with Hearing Impairment Reading Achievement Questionnaire (SHIRAQ) (r-0.82). Three research questions were answered. The data collected were analysed using frequency count, percentage, Pearson Product Moment Correlation and Multiple Regression. Results showed that there was a positive relationship between attitude, self-concept, self-efficacy, parental involvement, teachers-students interaction, parents' socio-economic status and reading achievement. Also, there was significant joint contribution of attitude, self-concept, self-efficacy, parental involvement, teachers-students interaction, parents' socio-economic status to reading achievement among students with hearing impairment. There was relative contribution of attitude, self-concept, self-efficacy, parental involvement, teachers-students relationship and parents' socioeconomic status to reading achievement. It was recommended that students with hearing impairment should be provided with textbooks and other educational facilities by their parents and-the government.